Testing the consistency of dust laws in SN Ia host galaxies: a BayeSN examination of Foundation DR1. Issue 3 (5th October 2021) - Thorp, Stephen; Mandel, Kaisey S; Jones, David O; Ward, Sam M; Narayan, Gautham
ABSTRACT: We apply BayeSN, our new hierarchical Bayesian model for the SEDs of Type Ia supernovae (SNe Ia), to analyse the griz light curves of 157 nearby SNe Ia (0.015 < z < 0.08) from the public Foundation Supernova Survey data set. We train a new version of BayeSN, continuous from 0.35 to 0.95 μ m, which we use to model the properties of SNe Ia in the rest-frame z -band, study the properties of dust in their host galaxies, and construct a Hubble diagram of SN Ia distances determined from full griz light curves. Our griz Hubble diagram has a low total RMS of 0.13 mag using BayeSN, compared to 0.16 mag using SALT2 . Additionally, we test the consistency of the dust law RV between low- and high-mass host galaxies by using our model to fit the full time- and wavelength-dependent SEDs of SNe Ia up to moderate reddening (peak apparent B − V ≲ 0.3). Splitting the population at the median host mass, we find RV = 2.84 ± 0.31 in low-mass hosts, and RV = 2.58 ± 0.23 in high-mass hosts, both consistent with the global value of RV = 2.61 ± 0.21 that we estimate for the full sample. For all choices of mass split we consider, RV is consistent across the step within ≲ 1.2σ. Modelling population distributions of dust laws in low- and high-mass hosts, we find that both subsamples are highly consistent with the full sample's population mean μ( RV ) = 2.70 ± 0.25 with a 95 per cent upper bound on the population σ( RV ) < 0.61. The RV population means are consistent within ≲ 1.2σ. We find that simultaneous fitting of host-mass-dependent dust properties within our hierarchical model does not account for the conventional mass step.